Strike And Power(Lessness) Of The Union - Zoran Stojiljković (Srpska Politička Misao)
The aim of this paper is to identify, on the basis of an analysis of the causes, the course and effects of strikes in Serbia over the last three decades, the mechanisms by which society and trade unions have moved from self-management mythology to the defense of whatever wages and “decent, dignified work” as the maximum goal. The drama of the decay of labor and trade unions, as well as the crisis of society, is presented in three chronologically related acts. The first one describes the process of decay concealed behind the call for patriotism, a kind of socialist-patriotic deception. The second one is the democratic introduction of capitalism through “predatory privatization”. The current, third act, illustrates how neoliberal populism seeks to pacify any resistance of employees and autonomous unions by creating their surrogates through political clientelism and party employment.